Semi-Arid Environmental Conditions and Agronomic Traits Impact on the Grain Quality of Diverse Maize Genotypes - Bongianino, Nicolás Francisco (2024)
We assessed the impact of environmental conditions and agronomic traits on maize grainquality parameters. The study was conducted using genotypes with distinct genetic constitutionsdeveloped specifically for late sowing in semi-arid environments. We evaluated the agronomic,physical, and chemical characteristics of eight maize open-pollinated varieties, six inbred lines, andthree commercial hybrids. The yield of the open-pollinated varieties showed a positive correlationwith protein content (r = 0.33), while it exhibited a negative correlation with the carbohydratepercentage (r = −0.36 and −0.42) in conjunction with the inbred lines. The flotation index of thehybrids was influenced primarily by the environmental effect (50.15%), whereas in the inbred lines itwas nearly evenly divided between the genotype effect (45.51%) and the environmental effect (43.15%). In the open-pollinated varieties, the genotype effect accounted for 35.09% and the environmental effect for 42.35%. The characteristics of plant structure were associated with grain quality attributes relevant for milling, including hardness and test weight. Inbred lines exhibited significant genotype contributions to grain hardness, protein, and carbohydrate content, distinguishing them from the other two germplasm types. These associations are crucial for specific genotypes and for advancing research and development of cultivars for the food industry.